Cognitive Flexibility Training Improves Extinction Retention Memory and Enhances Cortical Dopamine With and Without Traumatic Stress Exposure - Chaby, Lauren E.; Karavidha, Klevis; Lisieski, Michael J.; Perrine, Shane A.; Liberzon, Israel (Frontiers in Behavioral Neuroscience, 2019)
Stress exposure can cause lasting changes in cognition, but certain individual traits, such as cognitive flexibility, have been shown to reduce the degree, duration, or severity of cognitive changes following stress. Both stress and cognitive flexibility training affect decision making by modulating monoamine signaling. Here, we test the role cognitive flexibility training, and high vs. low cognitive flexibility at the individual level, in attenuating stress-induced changes in memory and monoamine levels using the single prolonged stress (SPS) rodent model of traumatic stress in male Sprague-Dawley rats. Exposure to SPS can heighten fear responses to conditioned cues (i.e. freezing) after a fear association has been extinguished, referred to as a deficit in extinction retention. This deficit is thought to reflect an impairment in context processing that is characteristic of posttraumatic stress disorder (PTSD). During the cognitive flexibility training we assessed individual variability in cognitive skills and conditioned rats to discriminately use cues in their environment. We found that cognitive flexibility training, alone or followed by SPS exposure, accelerated extinction learning and decreased fear responses over time during extinction retention testing, compared with rats not given cognitive flexibility training. These findings suggest that cognitive flexibility training may improve context processing. Individual performance during the reversal phase of the cognitive flexibility training predicted subsequent context processing, in that individuals with high reversal performance exhibited a faster decrease in freezing responses during extinction retention testing. Thus, high reversal performance predicted enhanced retention of extinction learning over time and suggests that cognitive flexibility training may be a strategy to promote context processing. In a brain region vital for maintaining cognitive flexibility and fear suppression, the prelimbic cortex, cognitive flexibility training also lastingly enhanced dopamine and norepinephrine levels, in animals with and without traumatic stress exposure. In contrast, cognitive flexibility training prior to traumatic stress exposure decreased levels of dopamine and its metabolites in the striatum, a region mediating reflexive decision making. Overall, our results suggest that cognitive flexibility training can provide lasting benefits by enhancing extinction retention, a hallmark cognitive effect of trauma, and prelimbic dopamine, which can maintain flexibility across changing contexts.